Pengetahuan Bahaya Kebakaran Dengan Perilaku Pengendalian Kebakaran Di PT Indo Acidatama TBK Karanganyar - Yeremia Rante Ada; Rena Ayu Wulandari (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
The chemical industry is an industry that involves chemical substances in the manufacturing process. Industries that produce or manage chemical-based materials are categorized as having a high level of fire risk. Based on materials and production products that come from flammable materials that have potential fire and explosion hazard caused by machines, unsafe workplaces and unsafe action. This research aims to determine the correlation between the level of knowledge of fire hazards with fire control behavior. The method in this research is an analytical observational research method with a cross-sectional approach. The respondents in this study were employees of PT Indo Acidatama Tbk in the Mechanical and Electrical department with a population of 55 respondents. The sampling technique uses the total sampling technique. The measuring instrument in this research is a questionnaire to measure the level of knowledge of fire hazards and also fire control behavior that have been tested for validity and reability with a cronbach alpha value =0.876. The data analysis technique used is the Somers'd correlation test analysis. The results of the Somers’d correlation test indicate that there is a significant correlation between the variables level of knowledge of fire hazards with fire control behavior with a significance value of p value =0.000 (p value <0.05), and a correlation coefficient value of r =0.838 with a positive correlation direction (+). There is a significant correlations between the level of knowledge of fire hazards with fire control behavior with a positive relationship direction. Improved knowledge will improve occupant control behavior in fire control.